Piecemeal Mechanism Combining Sprouting and Intussusceptive Angiogenesis in Intravenous Papillary Formation Induced by PGE2 and Glycerol. Issue 10 (5th May 2017) - Díaz‐Flores, Lucio; Gutiérrez, Ricardo; García, M. Del Pino; Sáez, Francisco J.; Díaz‐Flores, Lucio; Madrid, Juan F.
ABSTRACT: Recently, we demonstrated that in human intravascular papillary endothelial hyperplasia (IPEH), vein wall vascularization occurs in association with myriad papillae, a large part of which formed in the vascularized vein wall. Previously, using an animal model, we observed that PGE2 and glycerol administration around the femoral vein originates intense vascularization of the vein wall from its intimal endothelial cells (ECs). This vascularization is similar to that in IPEH. The aim of this study is to assess the mechanism of papillary formation, using this model after demonstrating papillary development in neo‐vascularized femoral vein walls. In semithin and ultrathin sections, the sequential vascular and papillary development was as follows: (a) activation of vein intimal ECs, (b) sprouting of intimal ECs towards the vein media layer and microvessel development, (c) interconnection between neighboring microvessels originated elementary loops, which encircled vein wall components and formed papillae. The encircling ECs formed the papillary cover, and the encircled component formed the core. The papillae showed a similar structure to that of folds and pillars in intussusceptive angiogenesis, and (d) origin of secondary and complex loop systems by interconnection of neighboring elementary loops and by splitting of papillae by new loops, with abundant papillary development. In conclusion, the results support a piecemeal angiogenic mechanism in papillary formation, with association of sprouting and intussusceptive types of angiogenesis. Further studies are needed to assess whether the intravascular papillae described in several pathologic processes, including vessel tumors, such as Dabska's tumor, retiform hemangioendothelioma, and angiosarcoma, follow a similar mechanism. Anat Rec, 2017. © 2017 Wiley Periodicals, Inc. Anat Rec, 300:1781–1792, 2017. © 2017 Wiley Periodicals, Inc.